Analysis of Electrical Network Reliability and K3l Risk Management Using Fmea and Hirarc at PT PLN (Persero) ULP Trade - Ahmad Budiarto; Rahmaniar Rahmaniar; Hamdani Hamdani (INFOKUM, 2026)
The reliability of the electricity distribution network and the implementation of Occupational Safety and Health (K3L) are crucial factors in maintaining the continuity of electricity supply and minimizing the risk of work accidents. This study aims to analyze the risk management of electrical network disruptions at PT PLN (Persero) ULP. The trading period of July–December 2025 used the Failure Mode and Effect Analysis (FMEA), Hazard Identification, Risk Assessment and Risk Control (HIRARC), and Integrated Risk Framework (IRF) methods. Data were collected through field observations, structured interviews, and documentation of disruption reports. The Risk Priority Number (RPN) value was calculated based on the parameters of Severity, Occurrence, and Detection, while the K3L Risk Rating (RR) was obtained from the multiplication of Severity and Likelihood. The results showed that the Short/Flashover Transformer had the highest Integrated Risk Index value of 3150 with the Critical category, followed by Broken Lightning Arrester (IRI=2940) and Broken HUTM Cable (IRI=2400) in the High Risk category. The integration of FMEA and HIRARC through the IRF approach has been proven to provide a more comprehensive basis for risk-based decision-making than using a single method, while strengthening the K3L management system and systematically improving the reliability of the distribution system.